Ameliorative Effect of Allium Cepa L. (Red Onion) Extract against Potassium Bromate Induced Intestinal Injury‏ In Rats - Kermani, Nadia M.; Abushofa, Fikry A; Adaek, Amera M.; Jaat, Fathia G.; Shakhtour, Fathia G. (Asian Journal of Pharmaceutical Research and Development, 2021)
Potassium bromate is an oxidizing agent and one of the cheapest dough improvers in the baking and food industry. This agent is classified as carcinogenic in rats and nephrotoxic in both man and experimental animals when given orally. The red onion, Allium cepa, is used in the daily diet for taste. Compounds in onions also have various medicinal properties, such as being anticancer, antifungal, antioxidant, anti-ulcer, and anti-inflammatory. We therefore sought to investigate whether aqueous extract of red onion would be protective against injury to the intestine Materials and Methods: 36 Wistar male rats were divided into 6 batches. Over a 4-weeks experimental period, group I rats served as a control and group II received 100 mg/kg b.w of KBrO3 on the 24th and 27th days. Group III received red onion juice at 1ml/100 g bw every day and 100 mg/kg bw of KBrO3 on the 24th and 27th days. Group IV received 50 mg/kg bw of KBrO3 twice per week, group V received red onion juice daily at 1ml/100 g bw and 50 mg/kg bw of KBrO3 twice per week, and group VI received 30 mg/kg KBrO3 every day. The body and four organs weights, including the kidney, testis, lung and liver of all experimental rats were measured. The histopathological investigation was performed for the intestine tissues of all groups. Results: KBrO3-treated small intestines exhibited destruction in the villi, decreased number of goblet cells, crypt loss and cell infiltration in the epithelial lining. Treatment with extract of red onion appeared to significantly ameliorate the toxic effects of KBrO3. Conclusion: Our findings suggest that red onion ameliorates the extent of intestinal injury and appears to act as an antioxidant. This study supports that red onion has beneficial properties, although no direct clinical conclusions can be drawn from these data.